Dramaturgy of Ferrol. The "Grupo Autónomo de Lectura de Obras" (GALO) - Oti Ríos, Francisco (Madrygal. Revista de Estudios Gallegos, 2018)
The aim of this project is to rescue one new page of the History of Theatre in Galicia and bring it closer to the society. A contribution that, in our view, is necessary to rebuild some passages of the Galician Theatre system consolidation process, which can be sometimes unknown or ignored, while there is no doubt they are part of it and, hence, its interest. Our investigation is focused on what we can consider the first group of dramatists from Galicia; half a dozen of people from the theatre world of Ferrol that decided to become a play-reading autonomous group in order to study the thematic and formal drama aspect of the texts, with the aim to disseminate their contributions among many Galician and foreign stakeholders through the use of archive-forms.